Growth following solid organ transplantation in childhood (Clinics, 2014)
One of the ultimate goals of successful solid organ transplantation in pediatric recipients is attaining an optimal final adult height. This manuscript will discuss growth following transplantation in pediatric recipients of kidney, liver, heart, lung or small bowel transplants. Remarkably similar factors impact growth in all of these recipients. Age is a primary factor, with younger recipients exhibiting the greatest immediate catch-up growth. Graft function is a significant contributing factor, with a reduced glomerular filtration rate correlating with poor growth in kidney recipients and the need for re-transplantation with impaired growth in liver recipients. The known adverse impact of steroids on growth has led to modification of the steroid dose and even steroid withdrawal and avoidance. In kidney and liver recipients, this strategy has been associated with the development of acute rejection. In infant heart transplantation, avoiding maintenance corticosteroid immunosuppression is associated with normal growth velocity in the majority of patients. With marked improvements in patient and graft survival rates in pediatric organ recipients, quality of life issues, such as normal adult height, should now receive paramount attention. In general, normal growth following solid organ transplantation should be an achievable goal that results in normal adult height.